2010
DOI: 10.1371/journal.ppat.1001070
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Synthases from Saprolegnia Are Involved in Tip Growth and Represent a Potential Target for Anti-Oomycete Drugs

Abstract: Oomycetes represent some of the most devastating plant and animal pathogens. Typical examples are Phytophthora infestans, which causes potato and tomato late blight, and Saprolegnia parasitica, responsible for fish diseases. Despite the economical and environmental importance of oomycete diseases, their control is difficult, particularly in the aquaculture industry. Carbohydrate synthases are vital for hyphal growth and represent interesting targets for tackling the pathogens. The existence of 2 different chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 53 publications
3
76
0
Order By: Relevance
“…Heterologous expression and in vitro biochemical assays have revealed that the CHS2 gene from Saprolegnia monoica actually encodes a functional CHS enzyme. The latter is inhibited by nikkomycin Z, a structural analogue of the chitin synthase substrate UDP-GlcNAc, which further supports the occurrence of chitin in this microorganism [16].…”
Section: Introductionsupporting
confidence: 62%
“…Heterologous expression and in vitro biochemical assays have revealed that the CHS2 gene from Saprolegnia monoica actually encodes a functional CHS enzyme. The latter is inhibited by nikkomycin Z, a structural analogue of the chitin synthase substrate UDP-GlcNAc, which further supports the occurrence of chitin in this microorganism [16].…”
Section: Introductionsupporting
confidence: 62%
“…This is illustrated by the case of pathogenic fungi, for instance, Candida albicans, in which 1,3-␤-glucan biosynthesis can be specifically blocked by drugs from the echinocandin family (10), thereby leading to cell death. In addition, our group has recently demonstrated the potential of targeting the biosynthesis of the minor chitin component in the oomycete Saprolegnia monoica for disease control (11).…”
mentioning
confidence: 99%
“…Recently, alternate chemical approaches have been tried to control S. parasitica infection with varying success, including chemically modified chitosans (27), peracetic acid (28), saprolmycins (29), oridamycins (30), Pyceze (2-bromo-2-nitropropane-1,3-diol) (12), and essential oils and ethanol extracts of medicinal plants (31). In addition, chitin synthases responsible for tip growth in Saprolegnia have been identified as potential targets for anti-oomycete drugs (32). Effective strategies and chemicals still need to be developed to control or eradicate Saprolegnia infections in aquaculture, especially in freshwater environments, with at least the same efficacy as malachite green.…”
mentioning
confidence: 99%